Comparison of Scar Modified Radical Mastectomy Surgery Using Songket Technique and Standard Technique in Dr. Mohammad Hoesin General Hospital in Palembang - Iqmal Perlianta; Rangga Kusuma Maulana; Mufida Muzakkie; Nur Qodir; Erial Bahar (Sriwijaya Journal of Surgery, 2020)
Introduction: Lateral ear dogs and loss of anterior axillary fold are side effects of modified radical mastectomy (MRM) operations and are cosmetically unpleasant. Songket technique is expected to reduce the side effects of MRM surgery. This study compared the Modified Radical Mastectomy surgery scar using Songket and standard techniques. Methods: This research is a clinical randomized trial. With anterior chest thoracic data of postoperative patients and assessed by the patient's family and medical professionals using a likert scale on wound length, wound width, wound angle and armpit folding. This study was performed in the Department of Surgery Mohammad Hoesin Hospital Palembang from January 2020 to April 2020. Results: A total of 32 research subjects participated with the average Likert scale score on medical and family assessments between the Songket and standard technique groups with p values ​​of 0.605 and 0.984, respectively. Conclusion: There was no difference in comparison of scar Modified Radical Mastectomy operations using Songket techniques and standard techniques at Mohammad Hoesin Hospital in Palembang.